The application of FT-IR reflection-absorption spectroscopy for determining the textural properties of copper oxide thin films - Švegl, Franc (Materiali in tehnologije, 2003)
Optical CuO coatings were deposited on different substrates with the wet chemistry route using a dip-coating technique. Studies of microstructure with SEM and TEM methods revealed that the films consist of spherical particles with diameters of about 50 nm. It was found that the thicker films exhibit a denser microstructure. From the determination of longitudinal optical modes (LO) of the CuO lattice by FTIR NGIA reflection-absorption spectroscopy and the phenomenon of the Berroman effect a method for qualitative and quantitative determination of the compactness of thin films was developed. The calculation of the optical constants (refractive index and absorption coefficient) for films having different thickness showed that the calculated refractive indices and the frequency shift of the CuO modes depend on the coating thickness and the density of the films. These results are in agreement with the observations of the microstructure and enable a quantitative estimation of the compactness of the CuO coatings.
Keywords: tanke plasti; bakrov oksid; optične lastnosti; FTIR spektroskopija; Berremanov pojav